(untitled) (Advances in Knowledge Representation, 2022)
Knowledge management involves the process of collecting, processing and disseminating the knowledge possessed by the company, with the aim of transforming itself into a more intelligent and competitive organization. Thus, this research sought to evaluate the results of the KMCanvas study focusing on the Kaizen continuous improvement tool in a knowledge management project in the mining sector. In the field research, a workshop was held to present KMCanvas and, after guidance, selected employees from two companies in the mining sector were asked to implement the model focused on Kaizen in a knowledge management project in organizations. Then, semi-structured interviews were carried out to identify the information for the satisfactory development of Kaizen activities with KMCanvas. As a result, the present research proved that KMCanvas is applicable to the reality of organizations, since it presents knowledge dissemination practices in a simple way and shows itself as an innovative choice to achieve competitive advantages.